Will the BEAUTIFUL Study results change our views on heart rate control? - Yu. M. Lopatin (Кардиоваскулярная терапия и профилактика)
The article describes the results of a randomized, double-blind, placebo-controlled, parallel-group BEAUTIFUL trial. The position of an If inhibitor ivabradine in the current algorithm of antianginal therapy is analyzed